William’s Flexion Exercise terhadap Intensitas Nyeri Haid (Dismenorea) pada Siswi - Yuni Indrawati; Wira Ekdeni Aifa; Fatma Nadia; Rifa Yanti (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of William's Flexion Exercise on the intensity of menstrual pain (dysmenorrhea) in female students at SMP Negeri 5 Batang Gansal, Indragiri Hulu Regency. The method used was a quantitative study with a quasi-experimental design using a one-group pretest-posttest. The results showed a significant decrease in menstrual pain intensity after William's Flexion Exercise (p-value < 0.05), indicating that the exercise reduced menstrual pain. This study concludes that William's Flexion Exercise is effective in reducing the intensity of menstrual pain (dysmenorrhea) in female students at SMP Negeri 5 Batang Gansal, Indragiri Hulu Regency. It can therefore be used as an alternative non-pharmacological therapy in managing dysmenorrhea in adolescent girls.   Keywords: Dysmenorrhea, Menstrual Pain Intensity, William's Flexion Exercise